Analisis Dampak Motivasi, Kualitas Pelayanan, Dan Kualitas Produk Terhadap Strategi Pengelolaan Usaha Cafetaria Di Kabupaten Lahat - Indra, Muhammad Halfi (Tourism, Hospitality And Culture Insights Journal, 2024)
This study aims to analyze the impact of motivation, service quality, and product quality on the business management strategy of cafeterias in Lahat Regency. In an era of increasingly intense business competition, cafeteria managers face the challenge of continuously improving product and service quality while understanding the importance of motivation in formulating effective strategies. This research employs a quantitative approach using a survey method, where data is collected through questionnaires distributed to managers and customers of cafeterias in Lahat Regency. Multiple linear regression analysis is used to test the impact of each variable on the business management strategy. The results of the study indicate that motivation has a significant effect on business management strategies, followed by service quality and product quality. This research provides valuable insights for cafeteria managers in formulating better strategies to enhance their business competitiveness by improving employee motivation, service, and product quality.